(untitled) (American Journal of Islam and Society, 2000)
l11e book is composed of an introduction, five chapters, a bibliography, and an index. In the first chapter, the author presents Malik Bennabi’s understanding of religion and its pace in human life. The second chapter outlines his views as to why human beings associate with each other and form societies. The third chapter deals with the constitution and dynamics of society as conceived by Bennabi. The fourth chapter is devoted to culture which features prominently in his writings. The final chapter discusses his cyclical theory of human sociocultural and historical development. The author informs us that he was introduced to Bennabi’s thoughts by reading his Le Phenomene Coranique (The Qur’anic Phenomenon). He was so impressed with Bennabi’s writing that when he contributed an article on the prospects of an Islamic theory of human society, he referred not only to the works of Ali Shariati, Muhammad Baqir as-Sadr, Murtaza Mutahhari, but also to Bennabi. An international seminar on Malik Bennabi held at the University of Malaya in Kuala Lumpur in 1991 gave him the opportunity to read a paper dealing with Bennabi’s contribution to social theory, in addition to inspiring ...